Influence of maternal thyroid hormones during gestation on fetal brain development. (7th February 2017) - Moog, N.K.; Entringer, S.; Heim, C.; Wadhwa, P.D.; Kathmann, N.; Buss, C.
Highlights: Thyroid hormones (THs) are crucial for key maturational processes during early brain development. Maternal TH deficiency during pregnancy may result in impaired offspring cognitive development. Gestational conditions related to stress may modulate maternal thyroid function. Abstract: Thyroid hormones (THs) play an obligatory role in many fundamental processes underlying brain development and maturation. The developing embryo/fetus is dependent on maternal supply of TH. The fetal thyroid gland does not commence TH synthesis until mid gestation, and the adverse consequences of severe maternal TH deficiency on offspring neurodevelopment are well established. Recent evidence suggests that even more moderate forms of maternal thyroid dysfunction, particularly during early gestation, may have a long-lasting influence on child cognitive development and risk of neurodevelopmental disorders. Moreover, these observed alterations appear to be largely irreversible after birth. It is, therefore, important to gain a better understanding of the role of maternal thyroid dysfunction on offspring neurodevelopment in terms of the nature, magnitude, time-specificity, and context-specificity of its effects. With respect to the issue of context specificity, it is possible that maternal stress and stress-related biological processes during pregnancy may modulate maternal thyroid function. The possibility of an interaction between the thyroid and stress systems in the context of fetal brain development has, however, not been addressed to date. We begin this review with a brief overview of TH biology during pregnancy and a summary of the literature on its effect on the developing brain. Next, we consider and discuss whether and how processes related to maternal stress and stress biology may interact with and modify the effects of maternal thyroid function on offspring brain development. We synthesize several research areas and identify important knowledge gaps that may warrant further study. The scientific and public health relevance of this review relates to achieving a better understanding of the timing, mechanisms and contexts of thyroid programing of brain development, with implications for early identification of risk, primary prevention and intervention.